Budd Chiari Syndrome in Children - Khadga, Mukesh; Hasan, Mahmudul; Rahman, AZM Raihanur; Ahamed, Nazmul; Md Benzamin, -; Rahman, Mohammad Ahmadur; Karim, ASM Bazlul (KYAMC Journal, 2020)
Budd-Chiari syndrome (BCS) is a rare disorder presenting with hepatic venous outflow obstruction from the level of the hepatic veins to the junction of the inferior vena cava (IVC) with the right atrium. It is rare in infants and children so, delay in diagnosis or misdiagnoses are very commonly seen. It results from either primary or secondary cause. Hypercoagulable state can be identified in majority of the cases. The clinical presentations may vary from asymptomatic to fulminant liver failure. A high index of suspicion and imaging findings may help in early diagnosis of this condition.Doppler ultrasonography can be the initial diagnostic investigation of choice.The treatment options include medical therapy along with surgical measures including liver transplantation for end-stage liver disease. KYAMC Journal Vol. 11, No.-1, April 2020, Page 46-49